Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, dan Proporsi Komisaris Independen terhadap Kinerja Perusahaan dengan Kualitas Laba sebagai Variabel Moderasi - Muhammad Alghifari Amchu; Ade Widiyanti; Reni Oktavia; Kamadie Sumanda Syafis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research explores the impact of institutional ownership, managerial ownership, and the proportion of independent commissioners on firm performance, with earnings quality serving as a moderating variable. The study draws on a sample of companies that undertook Initial Public Offerings (IPOs) in 2019 on the Indonesia Stock Exchange, utilizing data spanning the years 2019 to 2023. A multiple linear regression model was employed to assess both direct effects and interaction effects moderated by earnings quality. The findings indicate that institutional ownership and the presence of independent commissioners exert a statistically significant influence on company performance, with earnings quality enhancing these relationships. This study enriches the discourse on corporate governance mechanisms within newly public firms and offers practical insights for both market regulators and investors.